Tanggung Jawab Notaris/PPAT Atas Peralihan Hak Atas Tanah Yang Diklaim Sebagai Harta Pusaka Tinggi (Putusan Pengadilan Negeri Nomor 7/G/Pdt/2022/Pn.Pdg) - Komalasari, Nyi Mas (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Issues over customary land, particularly high-priority land in Minangkabau, often give rise to conflicts between customary law and national agrarian law. This is reflected in Padang District Court Decision Number 7/Pdt.G/2022/PN PDG, in which land traded through a Deed of Release of Rights and a Deed of Sale and Purchase (AJB) before a Notary/PPAT was claimed as high-priority land. This study aims to analyze the legal responsibilities of Notaries and PPATs in drafting deeds for customary land, as well as to provide legal certainty for buyers in good faith. The research method used is normative juridical, using a statute approach and a case approach. The results indicate a legal dualism between customary law and positive law, which leads to legal uncertainty in the transfer of land rights. Notaries and PPATs have formally exercised their authority in accordance with the law, but are still required to apply the principle of prudence to avoid being entangled in disputes. Meanwhile, legal protection for buyers in good faith remains weak when land is categorized as high heirloom land by the court.